LA PARIDAD DE MUJERES Y HOMBRES EN LA INSCRIPCIÓN DE CANDIDATURAS A DIGNIDADES DE ELECCIÓN POPULAR CONSTITUYE UN ACTO DE VIOLENCIA POLÍTICA QUE DEBE DEROGARSE - Yunga Uchuari., Mariuxi Yajaira (2019)
The present thesis entitled: "The parity of men and women in the registration of nominations for dignitaries of popular election constitutes an act of political violence that should be repealed", is the result of the study of a problem that negatively affects the citizenship, since with the obligatory parity the political participation of both men and women able to administer popular election posts, entrusted by the citizens by popular will, is prohibited. It is unavoidable to indicate that in the Electoral Organic Law, Code of Democracy, Article 3 stipulates Mandatory Electoral Parity, which establishes that within multi-person elections it’s alternating and sequential participation shall be mandatory, guaranteeing the participation of discriminated sectors through affirmative action measures. In this way, political participation is violent especially of women being used to fill the lists and not considered for their great leadership, administrative, economic, social and cultural management capacity. For this reason, I consider it necessary to repeal the mandatory parity at the time of registration of candidacies for popularly elected dignitaries. My research work contains conceptual references and doctrinal elements which allowed me to understand the legal problems.